Assessment of nutrient status in athletes and the need for supplementation - Larson-Meyer, D. E.; Woolf, K.; Burke, L. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Nutrition assessment is a necessary first step in advising athletes on dietary strategies that include dietary supplementation, and in evaluating the effectiveness of supplementation regimens. Although dietary assessment is the cornerstone component of the nutrition assessment process, it should be performed within the context of a complete assessment that includes collection/evaluation of anthropometric, biochemical, clinical, and environmental data. Collection of dietary intake data can be challenging, with the potential for significant error of validity and reliability, which include inherent errors of the collection methodology, coding of data by dietitians, estimation of nutrient composition using nutrient food tables and/or dietary software programs, and expression of data relative to reference standards including eating guidance systems, macronutrient guidelines for athletes, and recommended dietary allowances. Limitations in methodologies used to complete anthropometric assessment and biochemical analysis also exist, as reference norms for the athlete are not well established and practical and reliable biomarkers are not available for all nutrients. A clinical assessment collected from history information and the nutrition-focused physical exam may help identify overt nutrient deficiencies but may be unremarkable in the well-trained athlete. Assessment of potential food-drug interactions and environmental components further helps make appropriate dietary and supplement recommendations. Overall, the assessment process can help the athlete understand that supplement intake cannot make up for poor food choices and an inadequate diet, while a healthy diet helps ensure maximal benefit from supplementation. Establishment of reference norms specifically for well-trained athletes for the nutrition assessment process is a future research priority.